Social withdrawal and anxiety-like behavior have an impact on zebrafish adult neurogenesis - Perdikaris, Panagiotis; Prouska, Paulina; Dermon, Catherine R. (Frontiers in Behavioral Neuroscience, 2023)
Accumulating evidence highlights the key role of adult neurogenesis events in environmental challenges, cognitive functions and mood regulation. Abnormal hippocampal neurogenesis has been implicated in anxiety-like behaviors and social impairments, but the possible mechanisms remain elusive The present study questioned the contribution of altered excitation/inhibition as well as excessive neuroinflammation in regulating the neurogenic processes within the Social Decision-Making (SDM) network, using an adult zebrafish model displaying NMDA receptor hypofunction after sub-chronic MK-801 administration. For this, the alterations in cell proliferation and newborn cell densities were evaluated using quantitative 5-Bromo-2´-Deoxyuridine (BrdU) methodology, in short and long-term survival experiments. MK-801-treated zebrafish displayed decreased cell proliferation pattern within distinct neurogenic zones of telencephalic and preoptic SDM nodes, in parallel to the social withdrawal and anxiety-like comorbidity. BrdU+ cells co-expressed the pro-inflammatory marker IL-1β solely in MK-801-treated zebrafish, indicating a role of inflammation. Following the cessation of drug treatment, significant increases in the BrdU+ cell densities were accompanied by the normalization of the social and anxiety-like phenotype. Importantly, most labeled cells in neurogenic zones showed a radial glial phenotype while a population of newborn cells expressed the early neuronal marker TOAD or mGLuR5, the latter suggesting the possible involvement of metabotropic glutamate receptor 5 in neurogenic events. Overall, our results indicate the role of radial glial cell proliferation in the overlapping pathologies of anxiety and social disorders, observed in many neuropsychiatric disorders and possibly represent potential novel targets for amelioration of these symptoms.